Reduction in β− decay half-lives of highly ionized fission products - Gupta Arkabrata; Biswas Tripti; Lahiri Chirashree; Sarkar S. (EPJ Web of Conferences)
We calculate the rates of β− decay of highly ionized long-lived and medium-lived fission products (LLFPs, MLFPs). These elements, produced as residues of nuclear fission in reactors, exhibit high radioactivity and prolonged half-lives, making them hazardous to the environment. To address this issue of nuclear waste management, we theoretically investigate the effects of β− decay in highly ionized atoms. In the context of bare and highly ionized atoms, the presence of available phase space facilitates the generation of an electron within an unoccupied atomic orbital, a new channel of β− decay i.e., the decay to the atomic bound state, opens along with the usual continuum state decay. As a result, the total β− decay rate increases, significantly reducing the half-lives of the atoms, when they are made highly ionized or bare. In this work, we have calculated the total β− decay half-lives in the case of highly ionized LLFPs (79Se, 93Zr, 99Tc) and MLFPs (137Cs, 151Sm, 121Sn, 147Pm, 125Sb, 155Eu, 113Cd), taking the contribution of both, the decay from continuum and bound states. Our calculations show that there will be a noticeable reduction in the half-life of the considered nuclei for highly ionized atomic configurations.